Interspinous Dynamic Stabilization with DIAM (Silicone) or InSWing (PEEK) Interspinous Implants. (May 2014) - Berg, A. James; Tankel, J. A.; Hernandez, M.; Jensen, C. D.; Purushothaman, B.; Reddy, G. Raj; Friesem, T.
Introduction: Foraminal and spinal canal stenosis causes neurogenic claudication. Interspinous devices provide an indirect decompression by distracting the involved vertebrae, thereby tightening the buckled flavum and opening the foramina and attempting to restore normal loading patterns in the lumbar spine which have altered due to disc degeneration. When used for indirect decompression alone, they avoid scar tissue formation in the canal. The DIAM (Medtronic, United States) is made of silicone and therefore conforms more to the interspinous space. The InSWing (Orthofix, United States) is made of PEEK (polyether ether ketone) and is noncompressible. We report the outcomes between these devices and between direct and indirect decompressions. Materials and Methods: Retrospective analysis performed for surgery in July 2009 to 2011. Paired and unpaired t -test used to assess statistical significance ( p < 0.05). Results: A total of 60 patients were included (22 females, 38 males), age 46 (21-78) years. Preoperative duration of symptoms was 65 (4-420) months. The numbers in each implant/decompression group and follow-up are shown in Table 1. Statistically significant improvement observed in all outcome measures in direct and InSWing groups and all outcomes except MCS in DIAM group. Indirect group improved in all outcomes, but these were significant only in VAS Back/Leg. InSWing and direct group scores improved more than the DIAM and indirect groups, respectively, but these differences were only significant in Oswestry in the decompression group. All five patients requiring revision surgery were in the DIAM group. Conclusion: Statistically significant improvement was seen in all outcome measures in patients undergoing direct decompressions or implantation with InSWing implants. Improvement in scores was greater in these groups compared with the indirect decompression or DIAM groups. Disclosure of Interest A. Berg: None declared J. Tankel: None declared M. Hernandez: None declared C. Jensen: None declared B. Purushothaman: None declared G. Reddy: None declared T. Friesem: Conflict with RTI Surgical, Globus Medical